Dreamland Burning - Jennifer Latham (Brown Books for Young Readers, 2017)
When seventeen-year-old Rowan Chase finds a skeleton on her family's property, she has no idea that investigating the brutal century-old murder will lead to a summer of painful discoveries about the present and the past.